Concurrent execution of transactions in a peer-to-peer database network. (1st January 2011) - Masud, Mehedi; Aljahdali, Sultan
Transaction execution in a peer-to-peer database network specifies an update made to a peer's instance is applied to the peer's local database and propagated to related peers. Maintaining a successful execution of a transaction in such a network is challenging due to the dynamic behaviour of peers and unstructured topologies of networks. In this paper, we present a decentralised transaction execution process that guarantees the correct execution of a transaction without relying on any global coordinator. In the network, a peer executes a transaction and provides the local execution information to the initiator of the transaction. The initiator of a transaction plays important roles for the successful execution and termination of a transaction. Transactions originated from different peers may involve in a conflict during their execution in the network. In this paper, we also show a process to resolve conflicts using a universal leader election algorithm, called Mega-Merger.